KONSEP PENDIDIKAN NATURALISTIK JEAN JACQUES ROUSSEAU DAN RELEVANSINYA BAGI PENGEMBANGAN SISTEM MERDEKA BELAJAR DI INDONESIA - Siswadi, Gede Agus (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2023)
The current educational orientation is more toward a mechanistic education system. That is, the entire series of education carried out has been designed and very structured. So that teachers and students only follow the previously designed structure. Thus, the meaning of education that expects the development of the potential possessed by students will be hampered because of the structure that has been made. In understanding the reality of the world, students are kept away from their world. So that what is born is students who learn and understand about nature, but never learn together with nature. And Jean Jacques Rousseau presents the concept of naturalistic education as a rationale for returning students to natural reality. Through qualitative research methods with a philosophical hermeneutic approach, this study will attempt to uncover the meaning behind the reality of the world of education today by exploring the concept of naturalistic education initiated by Jean Jacques Rousseau. Thus, the results in this study indicate that Rousseau's idea of ​​the concept of naturalistic education departs from his concern about the direction of education which hinders the development of the potential of students in accordance with their natural nature. Students are likened to a robot that only follows the learning programs that have been designed. Thus, education must be returned to the natural aspect, so that students understand the realities of the world well. As well as the development of a “Merdeka Belajar” system in Indonesia, it is very important to understand Rousseau's concept of naturalistic education, so that it fully gives freedom to students to return to the natural nature of each student.